2022
DOI: 10.1002/cnma.202200199
|View full text |Cite
|
Sign up to set email alerts
|

Fe‐Incorporated Ni3S4/NiS2Nanocomposite as an Efficient Electrocatalyst for Alkaline Water Oxidation

Abstract: We report the development of iron-incorporated nickel sulfide (FeÀ Ni 3 S 4 /NiS 2 ) nanocomposite through sulfurization of iron incorporated nickel hydroxide precursor by using simple solvothermal method. The formation of Ni 3 S 4 / NiS 2 mixed-phase material was confirmed by PXRD analysis and the presence of multiple oxidation states of Ni (II and III) and incorporated Fe (III) was revealed by XPS studies. The electrochemical studies demonstrated that FeÀ Ni 3 S 4 /NiS 2 electrocatalyst has a high catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…This catalytic transformation is analogous to previous nickel chalcogenide literature where catalytic materials are usually converted into active NiOOH species during the OER. 76,79–81 The post-stability EDS study of NiS revealed the presence of O and the absence of S, which additionally supports the etching of sulfur moieties during OER and validates the XPS results (Fig. S38, ESI†).…”
Section: Resultssupporting
confidence: 80%
“…This catalytic transformation is analogous to previous nickel chalcogenide literature where catalytic materials are usually converted into active NiOOH species during the OER. 76,79–81 The post-stability EDS study of NiS revealed the presence of O and the absence of S, which additionally supports the etching of sulfur moieties during OER and validates the XPS results (Fig. S38, ESI†).…”
Section: Resultssupporting
confidence: 80%